PRODUKSI SIRUP GLUKOSE DARI PATI SECARA ENZYMATIK - Supriyo, Edy; Kurniawan, Dedy (Universitas Diponegoro, 2009)
Abstract In the prodacution of tapioca starch, before the starch being dried, glucose syrup could be produced wih ghigh concentrotion of maltose and glucose using enzymatic processes. Hidrolized tapioca starch using a-amylase enzyme which comes from Aspergilus niger produce concentration of syrup i.e. hanya 42,88 %, while using commercial a-amylase enzymes of NOVO (AMG 3001) the conversuion yiled was 114%. Beside the ash content is still high make the syrup colour become cloudy, whilst glucose syrup produced with a-amylase enzymee is very clear. Keywords : syrup glucosa, Aspergilus niger, a-amylase, tapioca starch